Strategi Penerjemahan Bahasa Indonesia–Arab terhadap Kualitas Penerjemahan - Istiqomah, Salma Nur; Salsabila, Salma; Shaqil, Sulthan Arifin; Al Farisi, Mohamad Zaka; Supriadi, Rinaldi (Study Program of Arabic Language Teaching, 2024)
This study aims to explore Indonesian-Arabic translation strategies and their impact on translation quality. Using a qualitative method based on a literature review, data were collected through documentation techniques involving selecting and analyzing relevant sources. The Miles and Huberman data analysis model included data reduction, presentation, and conclusion drawing. The research findings indicate that translation challenges include grammatical differences, ambiguities, cultural connotations, and meaning equivalence. Identified strategies include adaptation, amplification, reduction, domestication, and foreignization. Technology, such as online resources, also effectively supported the translation process. Moreover, a cultural approach and an in-depth understanding of the source text context are key to producing accurate and relevant translations. In conclusion, appropriate translation strategies and comprehensive contextual understanding are essential to improving the quality of Indonesian-Arabic translations. This study contributes to understanding effective translation practices and supports cross-cultural communication between these two languages.